A portable system for measuring cutaneous thresholds for warming and cooling. Issue 9 (September 1987) - Fowler, C J; Carroll, M B; Burns, D; Howe, N; Robinson, K
Abstract : Measurement of cutaneous thermal thresholds is a valuable technique for detecting small fibre neuropathy. A robust and portable microcomputer controlled system, which separately measures thresholds for warming and cooling, is described. Thresholds at three sites have been measured; the cheek, the dorsum of the hand and the sole of the foot. Regional variability and a correlation with age have been found, indicating the sensitivity of this system.